Readings from Emile Durkheim - Durkheim, Émile, 1858-1917 (Key texts., 2004)
"Emile Durkheim is regarded as a 'founding father' of sociology, and is studied in all basic sociology courses. This handy textbook provides a collection of the key passages from Durkheim's major works and successfully encapsulates the core of his sociology." "With this text, Kenneth Thompson has effectively filled a gap that previously existed in the literature available on Durkheim, by providing an outstanding collection of modern and reliable translations. Offering both in-depth coverage and useful reference, this text provides an indispensable aid to those seeking to gain access to Durkheim's writings."